Nigeria : index to federal acts, decrees and statutory instruments in circulation, 1989-2005 - Okubule, A. O. (Ibadan : Vantage Publishers, 2006)
This publication is a compilation of Decrees issued by the Federal Military Government of Nigeria from 1989 to 1999. It also contains Acts issued by the National Assembly from 2000 to 2005.
aug 22/05/13, ijb 03/04/2019
Loans
Keywords: Law; Delegated legislation